The Acceptance of Myths About Intimate Partner Violence Against Women (AMIVAW) Scale: Development and Validation in Spanish and English. (March 2018) - Megías, Jesús L.; Toro-García, Virginia; Carretero-Dios, Hugo
The measures available for assessing the acceptance of myths about intimate partner violence against women (AMIVAW) are characterized either by a lack of sufficient psychometric support or by being based on unclear theoretical propositions. In this article, we present a 15-item self-report scale: the Acceptance of Myths About Intimate Partner Violence Against Women (AMIVAW) Scale. We examined the reliability and validity of the scores of the Spanish and English versions of this scale across six different samples ( N = 1, 650) consisting of adult participants from Spain and the United States. Scores on both versions demonstrated high reliability. Results from exploratory and confirmatory factor analyses supported a one-dimensional structure. Invariance tests across genders demonstrated that the scale was invariant at the configural, metric, and scalar levels. The scale was also invariant at the configural level across countries. The AMIVAW scores were independent of social desirability, positively correlated with sexism and other scales used to measure attitudes toward abuse or sexual aggression, and negatively correlated with feminist ideologies. Finally, by using fictitious scenarios of intimate partner violence against women, we observed that participants with higher AMIVAW scores placed more of the blame on the victim and less responsibility on the perpetrator than those with lower AMIVAW scores. Taken together, the results provide strong validity evidence for the AMIVAW Scale. The AMIVAW Scale is a useful instrument to analyze the functions of myths in maintaining intimate partner violence against women. It is also a relevant tool for practitioners involved in programs to prevent and eradicate this form of violence.